Qudratic Programming with Max-Min Fuzzy Relation Equations Constraint - Xue-Gang Zhou (Fuzzy Information and Engineering)
In this paper, a new solution method of quadratic programming with max-min fuzzy relation equation constraint is put forward. Firstly, the optimal solution to some special fuzzy relation quadratic programming is researched. Secondly, some rules are presented to simplify the original programming. Finally, the new algorithm is given based on the simplified programming and the branch and bound method, the new algorithm does not need to find all feasible minimal solutions. Some numerical examples are given to illustrate the feasibility and effectiveness of the presented new algorithm.